Vam6 reduces iNKT cell function in tumor via modulating AMPK/mTOR pathways - Bai, Shiyu; Wu, Qielan; Zhu, Shasha; Zhang, Yuwei; Chen, Xuran; Su, Miya; Pan, Jun; Li, Shuhang; Yue, Ting; Xu, Linfeng; Xie, Di; Tian, Chenxi; et al. (Frontiers in Immunology, 2023)
Activation of mTORC1 is essential for anti-tumor function of iNKT cells. The mechanisms underlying impaired mTORC1 activation in intratumoral iNKT cells remain unclear. Here, we show that increased Vam6 expression in intratumoral iNKT cells leads to impaired mTORC1 activation and IFN- production. Mechanistically, Vam6 in iNKT cells is essential for Rab7a-Vam6-AMPK complex formation and thus for recruitment of AMPK to lysosome to activate AMPK, a negative regulator of mTORC1. Additionally, Vam6 relieves inhibitory effect of VDAC1 on Rab7a-Vam6-AMPK complex formation at mitochondria-lysosome contact site. Moreover, we report that lactic acid produced by tumor cells increases Vam6 expression in iNKT cells. Given the key roles of increased Vam6 in promoting AMPK activation in intratumoral iNKT cells, reducing Vam6 expression significantly enhances the mTORC1 activation in intratumoral iNKT cells as well as their anti-tumor efficacy. Together, we propose Vam6 as a target for iNKT cell-based immunotherapy.